Konseling Kelompok Untuk Meningkatkan Efikasi Diri Penyintas Covid-19 - Darmawansyah; Rufaidah, Anna; Nisa, Afiatin (Nosipakabelo: Jurnal Bimbingan dan Konseling Islam, 2022)
Self-efficacy is one of the important factors in healing the Covid-19 infection. In this case, group counseling was considered capable of increasing the self-efficacy of Covid-19 survivors. The aim of this study was to determine whether group counseling was able to increase the self-efficacy of Covid-19 survivors. This research was carried out using a quantitative approach with the type of experiment. The design used was the one group pretest-posttest design. The sample in this study was drawn randomly with a total of 10 people. Self-efficacy was measured using the GSE (General Self-efficacy) instrument. Data were analyzed using sign test. The results shown that group counseling was able to increase the self-efficacy of Covid-19 survivors. This increase further strengthens that counseling services can be used to help psychological barriers related to the Covid-19 pandemic.